Reduction method of external magnetic field effect on VR resolver - Makiuchi, Hiromi; Kikuchi, Yoshimi; Mimura, Hisashi; Kojima, Akira; Wakiwaka, Hiroyuki; Tashiro, Kunihisa (2009 IEEE Student Conference on Research and Development, 2009)
This paper deals with an angle accuracy of Variable Reluctance resolver to detect an angle of rotor about hybrid electric vehicle motor. Magnetic field effect was reduced by setting to long distance from the motor exciting coil, conventionally. However, it was found that magnetic field effect reduction method was accomplished by increasing of a back yoke thickness on the VR resolver stator by using finite element method.